Double trouble: Should double embryo transfer be banned? - Wilkinson, D; Schaefer, G; Tremellen, K; Savulescu, J (Springer Verlag, 2015)
What role should legislation or policy play in avoiding the complications of in-vitro fertilization? In this article, we focus on single versus double embryo transfer, and assess three arguments in favour of mandatory single embryo transfer: risks to the mother, risks to resultant children, and costs to society. We highlight significant ethical concerns about each of these. Reproductive autonomy and non-paternalism are strong enough to outweigh the health concerns for the woman. Complications due to non-identity cast doubt on the extent to which children are harmed. Twinning may offer an overall benefit rather than burden to society. Finally, including the future health costs for children (not yet born) in reproductive policy is inconsistent with other decisions. We conclude that mandatory single embryo transfer is not justified and that a number of countries should reconsider their current embryo transfer policy.